Juazeiro do Norte (Ceará, Brazil):: A Case of Urban (In)Sustentability - Nascimento, Diego Coelho do; Alves, Cicera Cecília Esmeraldo; Chacon, Suely Salgueiro (Sustainability in Debate, 2014)
This paper aims to study the city of Juazeiro do Norte, midsize city of the interior of Ceará; the prospects for urban sustainability in this metropolis. This is a qualitative research, fitting into the exploratory perspective. As methods and research techniques, we opted for the literature review, case studies and field visits. The city of Juazeiro do Norte experiences vigorous economic investments and large demographic expansion; however, still needs, urgently, reformulations in several segments, aiming to increase the quality of urban life and environmental conservation. We argue that the guiding direction that should govern the pursuit of urban sustainability is the transformation of the current progress in economic growth guided by a model of development truly sustainable.